Realization of Verbs in Ambon Malay - Firdawati Thenu; Jufrizal Jufrizal (English Language and Literature, 2022)
This study analyzed realization of verbs in Ambon Malay by using the theory of morphological typology. This research was conducted using the descriptive qualitative approach. The data were collected through questionnaire and elicitation techniques. Questionnaire was shared to 30 respondents, while interview was done with 6 informants. The two techniques were done by using three main instruments; interview guidelines, recording equipment, and writing equipment. An interactive model of data analysis was used to analyze the data. The data found in this study were 200 verbs in Ambon Malay. Only a small number of these verbs are inflected by four verb-formation affixes which are {meN-}, {baR-}, {taR-}, and {baku-}. These affixes are only attached to the current verbs. Whilst, most verbs are realized without affixes. This typical structure reflects that there must be morpheme deletion of prefix {di-}, suffixes {-i}, and circumfixes {di-kan}, {di-i}, {meN-kan}, {meN-i}, {memper-kan}, {memper-i} in Ambon Malay. Thus Ambon Malay is categorized as a semi-isolating language.